Avaliando a qualidade da internet banda larga ADSL no município de Passo Fundo - Silva, Silvano Elias da (2020)
This work aims to investigate how resources of problems occurred in a broadband operator of the ADSL Internet, a value of access to this information to mitigate failures in the service to its customers in the municipality of Passo Fundo and with the following benefits. As the methodological procedure is tested in DSLAM, which is a modem that is located in the telephone exchange, and distributes the broadband signal from the ADSL Internet, which in turn transmits these signals to telephone cabinets and, later, in boxes telephone lines located on street poles to the end customer's modem. The tests carried out were deferred and reproduced and, subsequently, the data collected were performed to identify the characteristics and quality of broadband Internet ADSL via metallic cable in the municipality of Passo Fundo / RS. The results obtained at the six stations showed that 50% of the total complaints are due to the item "no internet signal". Like these descents, at the São Cristovão station, or the main problem identified was defects in the secondary, at the Centro 1 station, with broken cables, and at the Centro 2 station, with problems in the DSLAM that serves this region. after identified as the main failures and causes, it can be concluded that the greatest occurrence of defects is the lack of preventive maintenance by the telephone and internet operator analyzed in this research, in order to maintain or increase the satisfaction of its customer and end user.